The effect of BZT doping on phase formation, dielectric and ferroelectric properties of BNLT ceramics - Puripat Kantha (2018)
© 2015, Springer Science+Business Media New York. In this work, the effect of BaZr0.05Ti0.95O3 (BZT) doping on phase, dielectric and ferroelectric properties of a lead-free piezoelectric ceramic system of Bi0.4871Na0.4871La0.0172TiO3 (BNLT) was studied. The different amounts of BZT were incorporated into BNLT to form (1−x)BNLT–xBZT ceramics (when x = 0, 0.06, 0.09 and 0.12 mol fraction). The rhombohedral phase was presented in the pure BNLT ceramic, which changed into the tetragonal phase with BZT incorporation. The lattice parameters and unit cell volume increased with increasing BZT content. Grain sizes tended to decrease with increasing BZT content. The dielectric constant of the BNLT ceramic was enhanced by BZT incorporation. The dielectric constant was maximized with the 0.09BZT incorporation. The temperature of the dielectric peak of BNLT ceramic decreased while the degree of diffuse phase transition increased with BZT substitution. The polarization–electric field (P–E) curve measured at temperature above 30 °C was found to be slimmer with increasing BZT content. The remnant polarization of the BZT-incorporated ceramics decreased with increasing temperature. The observed results were believed to be caused by the lattice distortion and the enhanced cation disorders in A and B-site lattices due to the incorporation of Ba2+ and Zr4+ ions into A and B-site lattices, respectively, of BNLT perovskite structure.